A new Oreolalax (Anura: Megophryidae) from the Hoang Lien Range, northwest Vietnam - Nguyen, Luan Thanh; Tapley, Benjamin; Kane, Daniel; Tran, Tuyet-Dzung Thi; Cui, Jiaxin; Rowley, Jodi J. L. (Zootaxa, 2024)
The megophryid genus Oreolalax is comprised of 19 species, most of which are endemic to China. A single species, Oreolalax sterlingae, is the only member of the genus known from Vietnam. During fieldwork on Mount Po Ma Lung in the Hoang Lien Range of northwest Vietnam, we encountered individuals of both Oreolalax sterlingae and another, morphologically divergent species of Oreolalax. Analyses of morphological and molecular data reveal that these individuals represent a previously undescribed species of Oreolalax which we describe as new to science. The new species, Oreolalax adelphos sp. nov., is sister to Oreolalax xiangchengensis and can be diagnosed from all other congeneric species by the combination of the following characters: (1) SVL of adult male 38.0 mm, N=1; adult female 46.2 mm, N=1; (2) narrow supratympanic fold; (3) no visible tympanum; (4) head longer than wide; (5) vocal sac absent; (6) absence of subarticular tubercles on hands; (7) basal interdigital webbing on hind feet; (8) ventral surface mottled with grey and creamy white; (9) dorsal surface of head and body covered in rounded, evenly spaced and similar sized tubercles; (10) presence of dark bars on limbs; (11) greyish white and creamy white spots on the flanks, and (12) a bicoloured iris. Oreolalax adelphos sp. nov. is only known from a single site of high elevation bamboo forest, where it is sympatric with Oreolalax sterlingae. Both Oreolalax adelphos sp. nov. and O. sterlingae are almost certain to occur in neighbouring Jinping County in Yunnan Province, China. The new species of Oreolalax likely qualifies for being assessed as Data Deficient in accordance with the IUCN Red List of Threatened Species categories and criteria.